Effect of Design of Uniform Packing Characteristic to Improve Cooling Tower Performance - Muhaimin, Ahmad; Bin Sies, Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2025)
An experimental study of the effect of uniform packing design on cooling tower performance is presented in this thesis, with a focus on contrasting a newly developed Uniform Packing New Design (UPND) with a Previous Packing Design (UPPD) and a Non-Uniform Packing (NUP) configuration. Thermal performance is assessed under a range of operating conditions, including inlet water temperatures of 35°C, 43°C, and 50°C, and water flow rates ranging from 25 to 200 kg/h, using a laboratory-scale cooling tower apparatus (Model HE 152). The primary factors that were looked at were the tower characteristic (KaV/L) and the cooling efficiency. The results show that the UPND does much better than the UPPD in all tested conditions. The tower characteristic values were 0.35, 0.39, and 0.37, which is an improvement of 52%, 86%, and 76%, respectively. UPND also showed better cooling efficiency across the tested temperature range, with values of 64.59%, 57.05%, and 54.89%, which was up to 54.3% better than UPPD. The better performance is due to better contact between water and air, a more even flow distribution, and the removal of thermal dead zones in the packing structure. NUP worked best at certain liquid-to-gas (L/G) ratios, but UPND worked well and consistently over a wider range of L/G ratios (0.20 to 1.70), showing that it can handle changing load conditions. The study finds that the uniform packing design not only improves heat rejection and thermal stability, but it also fits with sustainable energy goals by lowering entropy generation and fan energy use. These results show that UPND is a practical and high-performance option for industrial cooling systems. They also help make cooling tower technologies that are more efficient, reliable, and good for the environment.